Femmes, genre, féminisme - Trat, Josette (Les cahiers de "Critique communiste", 2007)
"Le retour sur l'histoire du courant féministe "lutte de classes" met en évidence l'urgence à penser les rapports sociaux de sexe en les articulant aux rapports de classe et aux rapports Nord-Sud. Quels sont les apports et les limites du Queer pour penser le genre et les oppressions? Quels sont les rapports entre les mouvements féministes et les mouvements gais et lesbiens? Quels sont les effets de la mondialisation néolibérale sur l'oppression des femmes et sur leurs luttes à l'échelle mondiale? Les questions des rapports de classe et celle du racisme ont été également remises au-devant de la scène par la révolte des banlieues dont les filles semblaient toutefois singulièrement absentes. Pourtant, elles luttent contre le sexisme, ainsi que le montre le collectif Féminin-Masculin de Vitry. A l'heure où les retours en arrière sont toujours possibles, comme en atteste l'émergence d'un mouvement masculiniste, la construction d'un courant féministe se donnant pour objectif de changer radicalement la société reste nécessaire pour gagner l'égalité réelle entre hommes et femmes."
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; histoire et politique; intersectionnalité; militance; premier cycle; queer; rapports de classe; rapports sociaux de sexe; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques